Metaforer och materialiseringar: Om apor hos Vladimir Nabokov och Sara Stridsberg - Björck , Amelie (Tidskrift för litteraturvetenskap, 2013)
Metaphors and Materializations. On the Apes and Monkeys in Vladimir Nabokov and Sara Stridsberg By tradition the humanities have been anthropocentrically focused on the lives of human beings in arts and literature. The limited analysis of what other species do in literature – and of the different relations between humans and animals that are represented – has sustained the notion of a hierachical divide between humans and other species, thereby reducing the ethical potential of literature to resist that dualism. The growing field of human–animal studies proposes that we return to our artefacts and epistemologies, with new attention to human–animal relations. Inspired by this movement, forefronted by scholars such as Cary Wolfe and Sara McHugh, this article offers a comparative reading of Vladimir Nabokov’s Lolita (1955) and Sara Stridsberg’s Darling River (2010). In Lolita Nabokov makes frequent use of animal and especially monkey metaphors, and carries out an ongoing animalization of his characters. In Stridsberg’s novel, which is written as a kind of hypertext of Lolita, Nabokov’s animalizations are interestingly molded and materialized into one physical creature: the caged schimpanzee Ester. The central concern of the study is to understand the process and effects of this materialization. I argue that the consequential reorientation of the reader to a non-hierarchical species discourse is a major ethical feat of the novel.